Local citizen participation in Uganda: Examining the political, administrative and financial aspects in Hoima district - David Mwesigwa; Mohammed Bogere; John Baptist Ogwal (Goodwood Publishing, 2022)
Purpose: This study aims to ascertain the impact of political, administrative and financial factors on local participants in Hoima district, Uganda. Research methodology: To ascertain the factors that impact participants in Uganda, a descriptive study was used in which primary data was analysed using descriptive statistics. Results: The factors were identified and clustered into thematic areas; they indicate a cluster of three factors appeared as themes. The results suggest that financial and political challenges are key impediments to effective participation and a good number of the technical personnel were not appointed on the basis of technical know-how. Hoima district needed to intensify its advocacy regarding increased central government transfers as well as the disbursements of more unconditional grants coupled with regular monitoring of its technical personnel. Limitations: The key limitation is the geographical scope since this study covered only one district, implying that the results cannot be generalized for the whole country. Contribution: The results of this are essential to academics in both Public Administration and Policy studies interested in enhancing local democracy and citizen-based governance.